2009
DOI: 10.1055/s-0029-1216389
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Medium Chain Triglycerides in the Treatment of Primary Intestinal Lymphangiectasia

Abstract: We conclude that, although an MCT diet is not completely curative in all cases, it does improve the symptoms of primary intestinal lymphangiectasia and reduces mortality. Hence it is a valid option in the paediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
0
33
0
3
Order By: Relevance
“…The principles of the treatment of PIL are different from those of other forms of protein-losing enteropathy, with no exact recommendations on the dosage and duration of therapy. A high-protein, lowfat diet, supplemented with medium-chain triglycerides, is currently the most effective and widely prescribed treatment, with minimal side effects [12]. In the present case, a low-fat diet, supplemented with medium-chain triglycerides, vitamins, and electrolyte supplements was introduced, with subsequent improvements in her clinical (abdominal pain and diarrhea, cured; lower leg edema, relieved) and laboratory data (hemoglobin [14.7 g/dL, total protein [5.1 g/L], albumin [2.6 g/dL], serum calcium [8.7 mg/ dL]).…”
Section: Case Reportmentioning
confidence: 99%
“…The principles of the treatment of PIL are different from those of other forms of protein-losing enteropathy, with no exact recommendations on the dosage and duration of therapy. A high-protein, lowfat diet, supplemented with medium-chain triglycerides, is currently the most effective and widely prescribed treatment, with minimal side effects [12]. In the present case, a low-fat diet, supplemented with medium-chain triglycerides, vitamins, and electrolyte supplements was introduced, with subsequent improvements in her clinical (abdominal pain and diarrhea, cured; lower leg edema, relieved) and laboratory data (hemoglobin [14.7 g/dL, total protein [5.1 g/L], albumin [2.6 g/dL], serum calcium [8.7 mg/ dL]).…”
Section: Case Reportmentioning
confidence: 99%
“…Consistent with these results, three of the patients in this study with IL had hypoalbumenia, lymphopenia, or chronic diarrhoea. Short-and medium-chain fatty acids are absorbed directly into the portal system without contributing to the formation of chylomicrons, thus providing energy and lessening lacteal engorgement and lymph loss [17]. A low-fat diet reduces lymphatic ow and pressure, preventing the lacteal dilatation and lymph leakage resulting from their rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of this treatment is accomplished through several mechanisms: the exclusion of long-chain fatty acids prevents congestion and rupture of dilated lymphatics; and MCTs directly absorb into the portal venous circulation, which avoids lymphatic vessel overload [4] . Desai et al [5] showed that this type of diet not only improves symptoms of the disease, but also reduces mortality. Based on the published study results, it was suggested that diet supplemented with MCTs should be continued as a lifelong therapy, regardless of the inadequate patient response.…”
Section: Discussionmentioning
confidence: 99%